Prevalência das infecções hospitalares em hospitais gerais de Belo Horizonte, 1992 - Edna Maria Rezende (1994)
In 1992 a prevalence survey of nosocomial infections (NI) was conducted in 11 general hospitals from Belo Horizonte. The aim was to dimension and better characterize the problem in hospitals this Brazilian region. Using a standard protocol, 2,339 patients were evaluated and 267 were found to have nosocomial infection which totalized a number of 328 episodes. The overall prevalence of NI was 14.0% and varied between hospitals from 4.6% to 27.3%. The most frequent type of hospital-acquired infections was pneumonia (19.5%) whith a prevalance of 2.74%, followed by surgical site infection (19.2%) with a prevalence of 2.69%. Taking only the surgical patients into consideration the prevalence of postoperative wound infection was 9.2%. Invasive procedures were observed in 58.4% of patients which were related with 16.1% of NI. The most important risk factor was the use of mechanical ventilation associated to nosocomial pneumonia. The highest rates were seen on intensive care unit (53.6%) followed by cardiovascular surgery service (31.9%) and pediatric service (27.2%). The microrganisms most frequently isolated from infected patients were Sthaphylacoccus aureus, Escherichia coli, Pseudomonas sp and Klebsiella sp. The use of antirnicrobials was observed in 42.8% of patients. The most used drugs were the cephalosporins (34,4%) followed by penicilljns (18.6%) and e aminoglycosides (15.1%).